Förlossningsbarnmorskors inifrånperspektiv av krav och kontroll – vad behöver stressinterventioner fokusera på? - Kandi,Karima (2017)
Working in labour units has been described as strenuous, and midwives are considered to need enhanced support from management. Several researches have argued that management however struggle to define occupational stress and invest in proper interventions for the employees based on their actual needs. More pragmatic research in the field has been requested. The first step forward is arguably to present data on personnel’s inside perspective of the issue, which subsequently can be utilized by management. The purpose of this study was to pragmatically investigate midwives’ perspective on demand and control as experienced in their work, and where midwives think the main source of the issue is. Semi-structured interviews were conducted and analysed using a thematic analysis. The findings showed that midwives experienced demands as multifactorial but that the leading source of strain were due to limits in control-latitude. Individual control-latitude was experienced as utilized, but organizationally governed control-latitude was considered so insufficient that the overall control-latitude often became too low to meet work demands. Inadequacies in the organizational governance increased the overall imbalance between work demands and control, but also prevented improvements for balance. Midwives described management’s influence regarding control latitude as significant and that decisions too often were conducted with lack of understanding of midwives’ real needs. The findings indicated that management’s governance over control latitude should increase united action with midwives to streamline intervention strategies.
Keywords: Förlossningsvården; barnmorskor; krav och kontroll; arbetsrelaterad stress; stressintervention; administrativ medicin; arbetsmiljöverket; organisatorisk och social arbetsmiljöföreskrifter; prioriteringar i hälso- och sjukvården; sjukvårdsutveckling.